Information security factors systematization - Янченко, Вадим Николавевич; Ивченко, Александр Владимирович; Залога, Вильям Александрович; Дынник, Оксана Дмитриевна (Technology audit and production reserves, 2015)
In this article the necessity of solving the theoretical and practical task, aimed on development the methodological basis for elaboration and implementation of information security management system, has been considered. Based on research results of scientific works and the requirements in the field of information security management the universal multilevel system of information security factors of organizations (enterprises) in the wood properties form was offered by using quality control theory and causal analysis. This system allows: to arrange factors in homogeneous characteristics; to demarcate the threats of the organization in the information security field by external and internal context; to determine the nature of the threats; to ensure the development of methodological fundamentals of creation and implementation the information security management system based on the integrated management system. The proposed system can be used as a tool for evaluation and/or reduction of information risks in organizations of various types, kinds and governance forms.